AN ANALYSIS OF THE DURATION AND IMPACT OF GADGET USE ONELEMENTARY SCHOOL STUDENT: ANALISIS DURASI DAN DAMPAK PENGGUNAAN GADGET PADASISWA SEKOLAH DASAR - Wira Surya Dinata Santoso; Tsabit aqdamal hasan; Tantowi Rista Adillah; Mohammad Ilham Fauzi; Arshy Prodyanatasari (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
In this modern era, gadgets have become an inseparable part of everyday life. The rapid development of software on gadgets allows us to access various applications for communication, entertainment, and learning. Gadget use is no longer limited to a certain age, so many children, including students at SDN Bandar Kidul 01 Kota Kediri, use gadgets in their daily activities. The problem that arises is how often the intensity of gadget use by elementary school students is and the impact it has on their lives. This research aims to analyze the duration of gadget use and its impact on students at SDN Bandar Kidul 01 Kediri City, with a focus on academic, health, and social aspects. The research was carried out through an outreach approach and filling out questionnaires by students as research subjects. The research results show that the average student uses gadgets for 1-2 hours per day, with the main aim of playing games and watching videos for entertainment. Negative impacts include decreased focus on learning for students, health problems such as eye fatigue for students, and reduced social interaction for students. On the other hand, the use of gadgets for educational applications is reported to support students' learning process. These results emphasize the importance of supervision from parents and teachers to regulate the use of gadgets wisely. With good time management, negative impacts can be minimized and the benefits of gadgets in supporting education can be optimized.